Maintenance bevacizumab following chemotherapy is associated with improved survival in patients with advanced and recurrent cervical cancer in a single-institution retrospective study - Johanna Kelley; Meng Yao; Danielle Chau; Sabrina Bedell; Melissa Yurch; Peter G. Rose; Michelle Kuznicki (Gynecologic Oncology Reports)
Objective: The objective of this study is to evaluate the patterns and outcomes of maintenance bevacizumab for patients with advanced or recurrent cervical cancer. Methods: This is a single-institution retrospective cohort study of patients who received clinical benefit from systemic therapy with bevacizumab from 2010 to 2022. Patients were divided into two cohorts: Cohort A received maintenance bevacizumab following therapy while Cohort B did not. Univariate Cox proportional hazards regression was performed to evaluate factors associated with progression free survival (PFS) and overall survival (OS) including age, stage, histology, hysterectomy, radiation, maintenance bevacizumab, and treatment line. Results: Of 53 patients, 15 patients were in Cohort A while 38 patients were in Cohort B. In Cohort A, 60 % had complete response to initial treatment, while only 34.2 % of Cohort B had complete response (p = 0.22). Of the ten (26.3 %) patients in Cohort B who developed a fistula, all had prior radiation. On univariate analysis, maintenance bevacizumab was associated with improved PFS (p = 0.002), and OS (p = 0.007), and up front treatment (rather than treatment for recurrence) and receipt of prior brachytherapy were associated with OS (p = 0.016 and p = 0.039, respectively). Median PFS with maintenance bevacizumab was 18.7 months vs 9.6 months, (HR 0.32, p = 0.002). Median OS for those receiving maintenance bevacizumab was 39.9 months vs 15.5 months, (HR 0.34, p = 0.007). Conclusions: Maintenance bevacizumab was associated with significantly prolonged PFS and OS in patients with advanced or recurrent cervical cancer who tolerated bevacizumab, but toxicity may preclude the use of maintenance therapy.